PENGARUH HANDOUT BERBASIS CERITA BERGAMBAR DALAM MODEL PEMBELAJARAN POE (PREDICTION, OBSERVATION, EXPLANATION) TERHADAP PENCAPAIAN KOMPETENSI IPA PESERTA DIDIK KELAS VII DI SMP N 7 PADANG - Kiroomin Barorotin Muji; Yurnetti Yurnetti; Letmi Dwiridal (Universitas Negeri Padang, 2016)
Creativity of educator in the learning process is the key to improve the competence of learners. One way is by developing teaching materials creatively to attract learners to learn. Using animated story based handout is an alternative to improve the competence of learners. This study aims to investigate the Effect of animated story based handout in POE's learning model to the achievement of student competencies at the SMP N 7 Padang. This research classified into Quasi Experiment research with Randomized Control Group Only Design. The research population was all students in grade VII registered in the academic year 2015/2016. The technique sampling was cluster random sampling.. Research data includes knowledge competencies, skills and attitude. The research instrument is in the form of a written test for competency knowledge, scorring rubric for competency skills and observation sheet for competence of attitude. Data were analyzed using statistical test of equality of two average (t-test) and chi square test. The result of the knowledge competencies show experimental class and control class different significantly on the real level of significant 0,05. This difference is believed to be the effect of the treatment given to the experimental class, so that it can be said that hypothesis is accepted. Then, for skills and attitude competence, data was analyzed using chi square test. The result shows there are no significant effect of using treatment given, so that it can be said that hypothesis is not accepted on the significance level 5% and dk 1